Virtual reality-based vestibular rehabilitation therapy in patients with acute unilateral vestibulopathy: a randomized controlled trial - Jae Woo Lee; Chul Young Yoon; Chul Young Yoon; Jae Ha Kim; Jae Ha Kim; Young Joon Seo; Young Joon Seo; Young Joon Seo; Tae Hoon Kong; Tae Hoon Kong; Tae Hoon Kong (Frontiers in Neurology)
IntroductionConventional vestibular rehabilitation therapy (VRT) requires significant time and resources, especially for patients with low compliance, limiting its effectiveness and accurate assessment. Studies have shown VRT using virtual reality (VR) to be effective, with meta-analyses confirming its superiority over conventional methods. However, methodological variations in VR remain a limitation. This study aimed to assess the effects of VRT using head-mounted display (HMD) VR technology in patients with acute unilateral vestibulopathy (AUVP) and compare the outcomes with conventional VRT.MethodsWe conducted a single-blinded randomized controlled trial with 60 AUVP patients randomly assigned to VR or control groups. The VR group received VRT via VR, while the control group underwent conventional VRT. Both groups followed individual home-based programs for 8 weeks and visited the clinic every 2 weeks. Subjective dizziness symptoms were evaluated using the visual analog scale (VAS), dizziness handicap inventory (DHI), and Activities-specific Balance Confidence (ABC) scale. Compliance with home-based programs was assessed on a 0–2-point scale based on responses in a booklet guide.ResultsSeven patients were lost to follow-up, leaving 26 and 27 patients in the VR and control groups, respectively. The mean patient age was 56.91 ± 12.11 years; 22 men and 33 women were included. Two-way repeated measures analysis of variance showed significant improvement in both groups for DHI and ABC scores. However, changes in DHI, VAS, and compliance scores did not differ between groups. Improvement in the physical domain of the DHI and ABC scores was significantly faster in the VR group (p = 0.019 for DHI, p = 0.0020 for ABC).DiscussionVRT using VR technology showed comparable efficacy to conventional VRT in AUVP patients. The VR group demonstrated greater improvement in the physical domain of the DHI and ABC scales, indicating enhanced confidence in movement and reduced perception of physical handicap due to dizziness.